Professional commitment and turnover intentions of elementary school teachers during educational crisis - Amir, Moran; Lipka, Orly; Sarid, Miriam (Frontiers in Education, 2025)
ObjectivesThis study examined professional commitment and turnover intentions among elementary school teachers in Israel during and after a period of educational disruption caused by COVID-19, investigating how demographic factors and satisfaction with life influenced these professional attitudes during systemic crisis.MethodsData were collected from 815 elementary school teachers at two time points: during the third COVID-19 lockdown (February 2021: T1, n = 395) and after returning to face-to-face teaching (June 2021: T2, n = 420) in Israel. Participants completed questionnaires measuring professional commitment, turnover intentions, and satisfaction with life. Analysis included independent t-tests to compare commitment and turnover intentions between time points, and hierarchical linear regression to identify predictors of professional commitment and turnover intentions.ResultsProfessional commitment levels remained stable across both time points, while turnover intentions significantly increased after returning to face-to-face teaching. Seniority emerged as a significant predictor of both commitment and turnover intentions, with less experienced teachers showing higher turnover intentions. Full-time employed teachers demonstrated fewer intentions to leave compared to part-time teachers. Teachers with advanced academic degrees (M.A.) showed higher dropout intentions. Life satisfaction positively predicted professional commitment and negatively predicted turnover intentions. The regression models explained 13.8% of the variance in professional commitment and 16.8% of the variance in turnover intentions.Conclusions and implicationsThis study uniquely contributes to the literature by examining teacher commitment and turnover through different phases of an educational crisis, providing novel insights into how the transition back to traditional teaching affects professional attitudes. The findings highlight the complex relationship between professional commitment and turnover intentions during systemic disruptions, particularly for vulnerable teacher subgroups with less seniority and advanced degrees. This research offers innovative guidance for developing targeted retention strategies, strengthening mentorship programs for new teachers, and creating career advancement opportunities within the education system—approaches that are crucial for maintaining workforce stability during and after educational crises.